Eficacia de 81 mg de ácido acetilsalicílico a dosis bajas en gestantes con Doppler anormal de arteria uterina en la prevención de preeclampsia - García Paredes Schönheit, Violeta De María (2020)
Hypertensive disorders of pregnancy are one of the leading causes of maternal and perinatal mortality worldwide. Preeclampsia has been estimated to complicate 2-8% of pregnancies globally. Currently, there is no effective drug for the treatment of pre-eclampsia; therefore, the alterations observed in the Doppler ultrasound images of the uterine artery may be the main key to predict adverse perinatal outcomes. The present work will be carried out to determine if treatment with 81 mg of acetylsalicylic acid (ASA) reduces the incidence of pre-eclampsia in pregnant women with abnormal Doppler flowmetry of the uterine arteries, reducing the incidence and complications of pre-eclampsia among pregnant women. The study will be a prospective observational cohort analytical study, which will include pregnant women who come for Doppler flowmetry evaluation in the first trimester and have abnormal Doppler flowmetry (mean pulsatility index) of the uterine arteries at the Víctor Lazarte Echegaray Hospital during the period April - December 2020 and who meet the selection criteria. A cohort study will be carried out in which the relationship between the variables will be evaluated by calculating the relative risk. The 95% confidence interval of the corresponding statistician will be calculated.